School Heads’ Financial Management and Program Implementation: Basis for Policy Recommendations - De Guzman, Charrize Anne (Journal of Interdisciplinary Perspectives, 2024)
As stewards of schools, school heads play a critical role in creating an enabling and supportive environment for effective teaching and learning. They work on all aspects of school administration. They are the school leaders overseeing the development and implementation of all educational programs and projects. This study examines the competence of school heads in financial management in selected public schools across the National Capital Region, focusing on planning, prioritizing needs, budgeting, monitoring, and evaluation. Using a descriptive quantitative research design, data was gathered from 350 respondents. Results showed that school heads were assessed as Highly Competent in financial management, with significant differences noted among the assessments of the three respondent groups regarding planning, monitoring, and evaluation. Additionally, implementing programs, projects, and activities, particularly in identifying priority areas, involving stakeholders, and allocating and utilizing funds, was rated as Highly Implemented. These findings highlight the critical role of school heads in addressing financial management challenges and informing policy recommendations to enhance their competence and the effective execution of educational programs.